1989
DOI: 10.1128/aac.33.3.362
|View full text |Cite
|
Sign up to set email alerts
|

Tissue concentrations and bioactivity of amphotericin B in cancer patients treated with amphotericin B-deoxycholate

Abstract: We have studied amphotericin B concentrations in tissues of 13 cancer patients who died after having received 75 to 1,110 mg (total dose) of amphotericin B-deoxycholate for suspected or proven disseminated fungal infection. Amphotericin B concentrations were measured by high-pressure liquid chromatography (HPLC) and by bioassay, the latter being done on tissue homogenates as well as on tissue methanolic extracts. The fungistatic and fungicidal titers of the tissue homogenates were also tested against three str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
3

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 16 publications
5
59
0
3
Order By: Relevance
“…This concentration is below the lowest level that produced toxicity in our study and far below the lethal levels in our study but may not represent the tissue concentration adjacent to the local depot. Collette et al [3] reported tissue concentrations of amphotericin B from intravenous infusion assessed with high-performance liquid chromatography of as high as 147 lg/g. The authors observed a correlation between increased amphotericin B delivery and increased fungistatic and fungicidal titer; however, the local toxicity of the amphotericin B was not evaluated as samples were taken from deceased subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This concentration is below the lowest level that produced toxicity in our study and far below the lethal levels in our study but may not represent the tissue concentration adjacent to the local depot. Collette et al [3] reported tissue concentrations of amphotericin B from intravenous infusion assessed with high-performance liquid chromatography of as high as 147 lg/g. The authors observed a correlation between increased amphotericin B delivery and increased fungistatic and fungicidal titer; however, the local toxicity of the amphotericin B was not evaluated as samples were taken from deceased subjects.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Amphotericin B, the standard therapy for aspergillosis, as well as itraconazole both have poor penetrance into the CNS. [31][32][33] Voriconazole has better penetrance 28 and may thus become the therapy of choice in patients with CNS aspergillosis. Recently, voriconazole has been found superior to amphotericin B in the primary treatment of invasive aspergillosis.…”
Section: Discussionmentioning
confidence: 99%
“…So far, no unequivocal advantage has been proved for any one type of drug therapy, neurosurgical procedure or combined treatment approach (Coleman et al, 1995). Itraconazole and amphotericin B, either as desoxycholate or encapsuled in liposomes, poorly penetrate across the brain-blood barrier (Como & Dismukes, 1994;Collette et al, 1989Collette et al, , 1991. Flucytosine may be recovered in high concentrations from the CSF, but aspergilli frequently show resistance to this drug (Francis & Walsh, 1992).…”
Section: Discussionmentioning
confidence: 99%